The Secondary Metabolite and Antibiotic Activity of Calabash Leaf and Fruit (Crescentia Cujete L) Ethanol Extract - Kianto Atmodjo; Boy Rahardja Sidharta (Seminar Nasional Penelitian dan Abdimas, 2023)
Antibiotic resistance is a big problem in medication, food security, and human development goals. Indonesia has a very huge diversity in term of medicinal plants, which are proven to cure many illnesses by their ancestors, including Calabash. However, research on the bioactive substances from the leaves and fruit of calabash as antibiotic [both antibacterial and antifungal] are dearth. Antibiotic activity test of the substances found has never been done yet, including the comparison to antibiotic ampicillin. The objectives of the research are: a] to determine bioactive substances found in the leaves and fruit of Calabash which have antibiotic activities, b] to reveal the antibiotic activity of leaves and fruit extract of calabash to two [2]] pathogenic bacteria and two [2] pathogenic fungus, c] to determine minimum inhibitory concentration [MIC] of calabash’s leaves and fruit extract to four [4] pathogenic microbes. The methods applied in this research are as follows. The bioactive substances were extracted using maceration method with ethanol as the solvent. The extracts were then analyzed using GC-MS equipment and tested to four [4] pathogenic microbes in agar diffusion method to determine the inhibition zones of the extracts. Later, the extract was also used to determine the MIC of the extracts by dilution technique. This present research found that fruit and leaves extract have many bioactive substances such as saponin, flavonoid, terpenoid and alkaloid that have low-medium antibacterial and antifungal activity, with minimum concentration of inhibition 50% for bacteria and 75% for fungus., which later can be developed into products or antibacterial and antifungal drugs that may give benefits to Indonesian people and the world.